2019
DOI: 10.1080/02670836.2019.1661649
|View full text |Cite
|
Sign up to set email alerts
|

Open-cell copper foam joining: Joint strength and interfacial behaviour

Abstract: A copper (Cu) foam was brazed with Cu-4.0Sn-9.9Ni-7.8P filler foil for joint strength and interface analysis. Brazed 50 pores per inch (PPI) Cu foam yielded a maximum compressive strength of 14.4 MPa with a 127% increment compared to nonbrazed Cu foam. 15 PPI Cu foam produced a maximum shear strength of 2.7 MPa. Scanning electron microscopy showed that the thickness of the brazed seam decreased with increasing the Cu foam's PPI. The formation of the Cu, Cu3P (P: phosphorus) and Ni3P (Ni: nickel) at the Cu/Cu f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Meanwhile, the light grey colour at the diffusion zone area indicated the enrichment with copper and tin (Sn) by spotting at points 2 and 11, and Sn was found near the end side of porous Ni, which can be seen in points 6 and 8. Tin was believed to have readily diffused from the VZ2250 BFM into porous Ni because Sn is a low melting-temperature metal and it is an active element, as well [22]. Tin and copper form a possible solid-solution phase of Cu-Sn.…”
Section: Microstructural Analysis Of Brazed Cu/porous Ni/ss304mentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the light grey colour at the diffusion zone area indicated the enrichment with copper and tin (Sn) by spotting at points 2 and 11, and Sn was found near the end side of porous Ni, which can be seen in points 6 and 8. Tin was believed to have readily diffused from the VZ2250 BFM into porous Ni because Sn is a low melting-temperature metal and it is an active element, as well [22]. Tin and copper form a possible solid-solution phase of Cu-Sn.…”
Section: Microstructural Analysis Of Brazed Cu/porous Ni/ss304mentioning
confidence: 99%
“…Besides this, nickel and phosphorus in the VZ2250 BFM diffused into the base metals (Cu and SS304) and porous Ni due to the concentration gradient to form the diffusion layer [25]. Furthermore, some of the phosphorus will evaporate due to its high vapour properties [26] and emerge in enriching copper and tin mostly in the porous Ni area, which resulted in the formation of brittle phases: Cu3P and Cu6Sn5 [22,26]. The Cu3P and Cu6Sn5 in the BFM have melted and coalesced with the porous Ni and base metal to form a strong and comparatively brittle joint.…”
Section: Microstructural Analysis Of Brazed Cu/porous Ni/ss304mentioning
confidence: 99%
See 1 more Smart Citation
“…The joining using Zn + 2% Al filler shows higher stiffness with the diffusion of Al-rich and Zn-rich in the joining area. Zahri et al (2019) found the strength of brazed Cu foam with a Cu-4.0Sn-9.9Ni-7.8P amorphous filler is dependent on the foam pore density. The diffusion of P and Ni elements into the foam allows it to coat the foam branches and leads to the increase in foam strength.…”
Section: Introductionmentioning
confidence: 96%
“…For electronic packaging solder joints, the performance of the solder material directly determines the performance of the solder joint [1,2]. The conventional SnPb solder is widely used, attributed to its low melting point and cost, as well as excellent wettability and mechanical properties [3].…”
Section: Introductionmentioning
confidence: 99%